The Application of The Principles of Justice, Legal Certainty, and Benefit in Regulating Civil Rights of Children After Divorce and Its Contribution to the Indonesian Legal System - Faiq Faiq; AH. Fathonih; Encup Supriatna; Syahrul Anwar (Locus: Jurnal Konsep Ilmu Hukum, 2025)
The high number of divorce cases in the jurisdiction of the Religious Courts under the Surabaya High Religious Court raises serious concerns about the civil rights of children post-divorce. In many cases, children's rights to maintenance, education, healthcare, and guardianship are neglected. This study aims to evaluate how the principles of justice, legal certainty, and benefit are implemented in legal decisions related to children’s civil rights after parental separation. Using a normative-empirical method with statutory, case, and comparative approaches, this study analyzes court rulings across various types of divorce cases within the Surabaya jurisdiction. The findings reveal a disparity in judicial considerations, particularly in child custody, maintenance, and guardianship rulings, reflecting the lack of consistency in substantive legal protection. While many decisions formally protect children’s rights, enforcement remains weak. The study concludes that institutional reform is needed to ensure the effectiveness of legal norms protecting children after divorce.